The McGurk effect is similar in native Mandarin Chinese and American English speakers - Magnotti, John F.; Basu Mallick, Debshila; Feng, Guo; Zhou, Bin; Zhou, Wen; Beauchamp, Michael S. (Frontiers in Psychology, 2025)
Humans combine the visual information from mouth movements with auditory information from the voice to recognize speech. A common method for assessing audiovisual speech perception is the McGurk effect: when presented with some incongruent pairings of auditory and visual speech syllables (e.g., the auditory speech sound “ba” dubbed onto the visual mouth movements for “ga”) individuals perceive a third syllable, distinct from the auditory and visual components. The many differences between Chinese and American culture and language suggest the possibility of group differences in the McGurk effect. Published studies have reported less McGurk effect in native Mandarin Chinese speakers than in English speakers, but these studies sampled small numbers of participants tested with a small number of stimuli. Therefore, we conducted in-person tests of the McGurk effect in large samples of Mandarin-speaking individuals from China and English-speaking individuals from the USA (total N = 307) viewing nine different stimuli. Averaged across participants and stimuli, we found similar frequencies of the McGurk effect between Chinese and American participants (48% vs. 44%). In both groups, there was high variability both across participants (range from 0% to 100%) and stimuli (14%−83%) with the main effect of culture and language accounting for only 0.2% of the variance in the data. The high variability inherent to the McGurk effect necessitates the use of large sample sizes to accurately estimate group differences and requires testing with a variety of McGurk stimuli, especially stimuli potent enough to evoke the illusion in the majority of participants.